A Pre-school Child of Initiative - Ewa Jagiełło; Anna Klim-Klimaszewska (Ignatianum University Press, 2017)
In the 21st century such words as saving money, financing and electronic money are very popular. It is difficult to discuss about functioning in the society without the ability to efficient movement in the field of finances. The need to propagate financial education since the early age is gaining popularity. This is strictly connected with the development of a wise consumer's attitude and the ability to manage in various financial situations, as well as passing respect towards money among small children. Both parents and teachers are responsible for promotion of economic ideas. Knowledge gained by children within every day's life is the source of information for forming financial programs. Children accompany their parents during visits at a bank, shop, post office and other institutions offering financial services. A pre- school child should not only know where such places are and how they look like, but also their duties and the basic rules of functioning. The following article has been devoted to such subject matter. It presents the list of words which are commonly used by children at the age of four or five. To collect the base of the words the method of brainstorm was used and the map of thoughts was created. Finally, the list of the subject matters within financial education for children of the pre-school age has been elaborated. Keywords: children, economic education, financial program, financial education, financial traps, financial language